Construction of hydrothermally stable beryllium phosphite open-frameworks with high proton conductivity. Issue 28 (6th July 2017) - Wang, Kangcai; Jin, Yunhe; Jiang, Linhai; Wang, Zhi; Zhang, Qinghua
Abstract : Two beryllium phosphite anionic open-frameworks based on Be3 P4 O12 H4 cluster building blocks were synthesized under solvothermal conditions. Both compounds displayed excellent hydrothermal stability and proton-conductive capacities. Abstract : Two new beryllium phosphite anionic open-frameworks based on Be3 P4 O12 H4 cluster building blocks, formulated as (Him)2 ·Be3 (HPO3 )4, were synthesized under solvothermal conditions, where im is imidazole. Interestingly, the use of different alcohols, i.e., isopropanol and n -propanol, as solvents afforded two new anionic open-frameworks with the same chemical composition, but different structures. Compound1 crystallized in the monoclinic C 2/ c space group, whereas compound2 crystallized in the triclinic P 1̄ space group. Both compounds displayed intersected channels with 8-, 8-, 8-, and 12-membered windows along different directions. Considering Be3 P4 O12 H4 clusters as four-connected nodes, both compounds showed a pcu topology. Notably, the frameworks of both open-frameworks remained stable after soaking in boiling water for one month. Furthermore, compound1 exhibited a high proton conductivity of 2.03 × 10 −3 S cm −1 at 363 K and 98% relative humidity, indicating its potential as a hydrothermally stable proton-conducting material.